FILOSOFI "TRI KAYA PARISUDHA" DALAM PENERAPAN SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN WP ORANG PRIBADI UMKM DAN PEKERJAAN BEBAS - Wulantari, Ni Putu Ayu Siska; Lesmana Putra, I Made Endra; Perdanawati, Luh Putu Virra Indah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.02.TAHUN. 2021, 2021)
Corona Virus Desease impacts all sectors and all levels of society without exception. This also has an impact on State revenues. As we know, the government enforces a Self Assessment System in its tax collection. The weakness of the self assessment system is that the taxpayer calculates, pays and reports taxes, in practice it is difficult to run as expected or even misused. The purpose of this study is to prove empirically that Tri Kaya Parisudha as a moderator of the influence of the Self Assessment System on the compliance of individual taxpayers who carry out business activities and independent work in Bali Province. Collecting data in this study using a questionnaire. The analysis technique used in this research is descriptive statistics and hypothesis testing using moderate regression analysis techniques. The conclusion of this study is that Tri Kaya parisudha does not moderate the effect of the implementation of self-assessment system on taxpayer compliance. Thinking and doing good during a pandemic cannot be used as a reference to make taxpayers obey. The difficulty of the community's economy can be a contributing factor. They tend to fulfill their basic needs first, then later they will be used to fulfill their tax obligations